2017
DOI: 10.1039/c7ce00751e
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and supramolecular assemblies of mono-hydroxylated octamethylcucurbit[6]uril with alkali and alkaline earth metal ions in the presence of polychloride cadmium anions

Abstract: The interactions of alkali metal and alkaline earth metal cations with (OH)OMeQ[6] have been investigated with polychloride cadmium anions as structure-directing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This phenomenon suggests a strong interaction between these components, which we interpret as an outer-surface interaction of the Q[ n ], including the π–π interaction of the carbonyl bonds of Q[7] with the aromatic rings of SC[4]A and ion–dipole interaction between the electropositive outer surface of Q[7] and the electronegative sulfonyl groups of SC[4]A. 57 To probe the interaction of Q[7] and SC[4]A in more detail, we first used a titration 1 H NMR technique to determine their interaction in neutral D 2 O. The experimental results showed that SC[4]A gradually disappeared from the solution with increasing number of equivalents of Q[7] and the ratio of precipitated Q[7] to SC[4]A was close to 3:1 (Figure S1 and Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon suggests a strong interaction between these components, which we interpret as an outer-surface interaction of the Q[ n ], including the π–π interaction of the carbonyl bonds of Q[7] with the aromatic rings of SC[4]A and ion–dipole interaction between the electropositive outer surface of Q[7] and the electronegative sulfonyl groups of SC[4]A. 57 To probe the interaction of Q[7] and SC[4]A in more detail, we first used a titration 1 H NMR technique to determine their interaction in neutral D 2 O. The experimental results showed that SC[4]A gradually disappeared from the solution with increasing number of equivalents of Q[7] and the ratio of precipitated Q[7] to SC[4]A was close to 3:1 (Figure S1 and Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…55,56 We ascribe such constructions to the so-called outer-surface interactions of Q[ n ], including C–H···π interactions between methine groups of glycoluril moieties of Q[ n ] and aromatic rings, π–π interactions between carbonyl groups of glycoluril moieties of Q[ n ] and aromatic rings, hydrogen bonding between methine groups of glycoluril moieties of Q[ n ] and protruded oxygen atoms of polyoxometallate anions or inorganic cluster anions, but mostly ion–dipole interactions between the electrostatically positive outer surface of Q[ n ]s and inorganic or organic anions. 57,58…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that CB [7] instantaneously self-assembles upon the addition of water soluble 4-sulfocalix4]arene (SC [4]A) leading to the formation of microcrystals in near-quantitative yield (>90%) in water [197]. This suggests that it was a strong outer-surface interaction of CB [7], i.e., π-π interaction of carbonyl bonds of CB [7] with aromatic rings of SC [4]A in addition to ion-dipole interaction between the electropositive outer surface of CB [7] with the electronegative sulfonyl groups of SC [4]A, respectively [198][199][200]. The as-formed inclusion complex (3:1) between CB [7] and SC [4]A was found to accommodate some volatile compounds e.g., polychloromethanes and also selectively absorbs certain organic dyes e.g., pyrenemethanamine hydrochloride, umbelliferone etc.…”
Section: Supramolecular Assemblies Between Two Hostsmentioning
confidence: 99%
“…Subtle differences in the outer‐surface electrostatic properties of Q[ n ] and i Q[ n ] result in significant differences in their chromatographic behavior . Q[ n ] and i Q[ n ] exhibit similar coordination properties, they can form coordination complexes with alkali metal cations, alkaline‐earth metal cations, and lanthanide cations in the presence of [M d‐block Cl 4 ] 2− , which acts as a structure‐directing agent, thereby forming a variety of supramolecular assemblies . However, the host–guest chemistry of i Q[ n ]s is quite distinct from that of Q[ n ]s. Isaacs and Kim have claimed that i Q[ n ]s can bridge and exceed the recognition properties of Q[ n ]s by displaying unprecedented size and shape selectivity .…”
Section: Figurementioning
confidence: 99%